Symmetric distortion in semiconductor laser and directly included at the microwave frequency - Ammar Zaker; Mzahim Azawi (مجلة التربية والعلم, 2007)
Abstract Characteristics of direct modulation of semiconductor laser microwave frequency were studied using the spectrum analyzer. The study showed the frequency distortion was greatly affected by the index of modulation, the laser diode temperature and the modulating frequency. The results indicated that the increase of distortion with frequency was found to be as (0.84 dB/MHz). On the other hand, the dependence of distortion on the index of modulation (m) showed that (m≤ 0.5) in order to keep the distortion as low as possible and a linear operation of laser diode.